Global environmental change - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 2002)
Annotation Presents an overview of the problems associated with global warming for scientists and engineers in industry, public service, consultancy, and academic institutions. Written by specialists in the field, the volume covers evidence for global warming, air pollution, rising sea levels, the effect of climate change on human health, and the role of environmental performance on industry. Distributed in the US by Springer Verlag. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Pollution -- Environmental aspects.; Climatic changes.; Environmental protection.; elektronické knihy; electronic books